Unidade de telemetria, armazenamento e visualização de dados embarcado em um carro de Fórmula SAE - Lauro, Luis Felipe Soto (2021)
The Society of Automotive Engineers has been promoting the Formula SAE competition since 1981 and gives young engineers the opportunity to take part in a complex and multidisciplinary project: the development of a competition car. Finding suitable tools and methods that enable validation through testing is fundamental to developing such complex projects. In this thesis, we develop a telemetry system to support the testing and validation of a Formula SAE monoseat car. We used a STM32F469I-DISCOVERY development board as an embedded processing unit and two CC13XX series radios from Texas Instruments to enable wireless communication with a remote station. To provide a user interface for data analysis, we developed a desktop application using the Qt framework. After validating the proposed tool in a relevant scenario, we found that it was able to collect, register and display (both locally and remotely) relevant data about the vehicle’s performance. This is of great importance for the continuous development of the project, especially for the monitoring and validation of all of its subsystems.